EGOISME DALAM PERSPEKTIF AL-QUR'AN: ANALISIS TEMATIK STRUKTURAL DENGAN PENDEKATAN GROUNDED THEORY - Eka Pratama; Muhammad Alif (CV. Adiba Aisha Amira, 2026)
This study aims to construct a Qur'anic conceptual model of egoism through a structural thematic analysis integrated with grounded theory coding procedures. Method: Employing a qualitative library research approach, this study analyzed twenty Qur'anic verses related to egoism selected through purposive thematic sampling. Data analysis followed three grounded theory coding stages: open coding to identify fundamental concepts, axial coding to establish thematic relationships between categories, and selective coding to integrate all categories into a unified conceptual model. Findings: The analysis identified five major categories constituting the structure of Qur'anic egoism: nafs management and self-discipline, social ethics and philanthropy, transformation from miserliness (bukhul), purification of the soul from arrogance (kibr), and existential orientation toward the hereafter. All categories converge under tawhid spirituality as the integrative core, distinguishing this model from secular Western paradigms that treat egoism as a neutral psychological drive. Recommendations: Future research is encouraged to develop empirical instruments and validate this conceptual model across educational, counseling, and Islamic psychotherapy settings.